‘We Came from a Faraway Place’: Narratives of Hebrew/Israelite and Egyptian Origin among the Ga Communities of Accra - Goshadze, Mariam (Journal of religion in Africa, 2026)
This article traces the historical construction and transformation of Hebrew/Israelite and Egyptian narratives of origin among the Ga people of Ghana. While claims of external ancestry are widespread in Africa, the Ga case remains relatively understudied. Emerging in seventeenth-century European travel accounts and later reinforced by missionary writings, the Hebrew/Israelite and Egyptian narratives were shaped by biblical frameworks that cast Ga religious practices as remnants of monotheistic traditions. From the late nineteenth century, Ga scholars and public figures began appropriating and reshaping these stories. Drawing on early European writings, missionary accounts, contemporary Ga perspectives, and ethnographic research, this article positions the Ga case within broader discussion of African historical consciousness and colonial knowledge production. It demonstrates that origin narratives are continuously reinterpreted in response to historical, intellectual, and political contexts, serving as tools of self-definition and negotiation with other cultural and religious groups.